The EDUKASI LITERASI KEUANGAN DALAM PENGELOLAAN KEUANGAN KELUARGA KEPADA GURU DAN ORANG TUA MURID DI TK RUSNIBRA JAKARTA - wulandari, Endang; Farida, Farida; Shidqi, Arrafi; Adjie Pratama, Muhammad (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The rapid development of digital technology, understanding financial literacy and management has become a crucial competency for parents and educators. This is especially important for managing household finances and preparing for children's future needs. Gold has emerged as a relatively easy investment option with a moderate level of risk. PT Pegadaian's Digital Gold Savings System was created to facilitate consumer investment in gold products. However, this new product is not yet widely known in the community. The purpose of this training is to provide theoretical knowledge about financial literacy and facilitate participants' hands-on practice using the Pegadaian Digital application to start investing in gold independently using their mobile phones. The methods used were outreach, hands-on practice, mentoring, and evaluation. The training resulted in 15 participants benefiting from increased knowledge of financial literacy and the ability to create gold savings accounts in the Pegadaian Digital application